Ameliorative Effects of Vitamin C in Cholpyrifos Induced Toxicity in Snow Trout (Schizothorax niger) - Rehman, Muneeb U.; Sheikh, Gowhar Gull; Ahmad, Bilal; Fatima, Bilquees; Ahmad, Sheikh Bilal; Mir, Manzoor ur Rahman (Indian Journal of Animal Nutrition, 2018)
The present study was carried out to investigate the ameliorative potential of vitamin C in chlorpyrifos induced toxicity in snow trout (Schizothorax niger). Forty healthy fishes were divided into 4 groups of ten fishes each. Group I was a normal control group (without chlorpyrifos and vitamin-C), group II was given chlorpyrifos at the dose of 0.075 mg/L without vitamin C, group III was exposed with chlorpyrifos at the dose of 0.075 mg/L and co treated with vitamin C (40 ppm) whereas group IV was exposed with chlorpyrifos at the dose of 0.075 mg/L and co treated with vitamin C (70 ppm). Treatment was continuously carried out for 41 days. Liver tissue homogenate was analyzed for antioxidant parameters. It was found that chlorpyrifos suppressed the antioxidant enzyme activity significantly and negatively affected the haematological parameters while supplementation with vitamin-C markedly improved the antioxidant status, hematological parameters and reduced the lipid peroxidation. The present study revealed that supplementation of vitamin-C in a balanced quantity can be a potent remedy for the protection of chlorpyrifos toxicity in fishes.